Intestinal Permeability and Circulating CD161+CCR6+CD8+T Cells in Patients With Relapsing–Remitting Multiple Sclerosis Treated With Dimethylfumarate - Buscarinu, Maria C.; Gargano, Francesca; Lionetto, Luana; Capi, Matilde; Morena, Emanuele; Fornasiero, Arianna; Reniè, Roberta; Landi, Anna C.; Pellicciari, Giulia; Romano, Carmela; Mechelli, Rosella; Romano, Silvia; et al. (Frontiers in Neurology, 2021)
Background: the changes of the gut-brain axis have been recently recognized as important components in multiple sclerosis (MS) pathogenesis. Objectives: to evaluate the effects of DMF on intestinal barrier permeability and mucosal immune responses. Methods: We investigated intestinal permeability (IP) and circulating CD161+CCR6+CD8+T cells in 25 patients with MS, who met eligibility criteria for dimethyl-fumarate (DMF) treatment. These data, together with clinical/MRI parameters, were studied at three time-points: baseline (before therapy), after one (T1) and 9 months (T2) of treatment. Results: At baseline sixteen patients (64%) showed altered IP, while 14 cases (56%) showed active MRI. During DMF therapy we found the expected decrease of disease activity at MRI compared to T0 (6/25 at T1, p=0.035 and 3/25 at T2, p<0.00), and a reduction in the percentage of CD161+CCR6+CD8+ T cells (16/23 at T2; p<0.001). The effects of DMF on gut barrier alterations was variable, without a clear longitudinal pattern, while we found significant relationships between IP changes and drop of MRI activity (p=0.04) and circulating CD161+CCr6+CD8+ T cells (p=0.023). Conclusions: the gut barrier is frequently altered in MS, and the CD161+ CCR6+CD8+ T cell-subset shows dynamics which correlate with disease course and therapy